Proteomic profiling and interactome analysis of ER-positive/HER2/neu negative invasive ductal carcinoma of the breast: towards proteomics biomarkers - Korwar, Arvind M.; Bhonsle, Hemangi S.; Ghole, Vikram S.; Gawai, Kachru R.; Koppikar, Chaitanyananda B.; Kulkarni, Mahesh J. (OMICS-A Journal of Integrative Biology, 2013)
Breast cancer, especially ER positive/HER2/neu negative IDC, is the predominant subtype of invasive ductal carcinoma. Although proteomic approaches have been used towards biomarker discovery in clinical breast cancer, ER positive/HER2/neu negative IDC is the least studied subtype. To discover biomarkers, as well as to understand the molecular events associated with disease progression of estrogen receptor positive/HER2/neu negative subtype of invasive ductal carcinoma, differential protein expression profiling was performed by using LC-MSE (MS at elevated energy). A total of 118 proteins were identified, of which 26 were differentially expressed. These identified proteins were functionally classified and their interactions and coexpression were analyzed by using bioinformatic tools PANTHER (Protein Analysis THrough Evolutionary Relationships) and STRING (Search Tool for the Retrieval of Interacting Genes). These proteins were found to be upregulated and were involved in cytoskeletal organization, calcium binding, and stress response. Interactions of annexin A5, actin, S100 A10, glyceraldehyde 3 phosphate dehydrogenase, superoxide dismutase 1, apolipoprotein, fibrinogen, and heat shock proteins were prominent. Differential expression of these proteins was validated by two-dimensional gel electrophoresis and Western blot analysis. The cluster of these proteins may serve as a signature profile for estrogen receptor positive/ HER2/neu negative subtype.